Pengembangan Video Tutorial Sebagai Penuntun Praktikum Bioteknologi Untuk Siswa Sekolah Menengah Atas : (The Development of Videos Tutorial as a Biotechnology Practicum Guide for High School Students) - Dewi Safitri; Suraida Suraida; Reni Safita; Boby Syefrinando; Mainingsih Mainingsih (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The purpose of this study was to design a video tutorial as a valid, practical, and effective biotechnology practicum guide developed for high school students (SMA).Â This type of research is R&D (Research and Development) with a 4D model (Define, Design, Development, and disseminate) This type of research is R&D (Research and Development) with the 4D model (Define, Design, Development, and Disseminate) which is limited to stage three.Â The instrument used in this research is a questionnaire.Â This research was conducted at MAN 1 Tanjung Jabung Timur on the subject of biology with a limited scale.Â The analysis is carried out in the form of curriculum analysis, teacher needs analysis, student needs analysis and student characteristics analysis.Â The assessment was carried out by three experts, namely material experts with a percentage of 89.5%, linguists with a percentage of 87.5% and design experts with a percentage of 95%.Â The tutorial video was tested with the teacher's response with a percentage of 92.2%.Â Then the video tutorial was tested on class XII semester II students with a practicality percentage of 97.9%, then the teacher's practicality level was 92.2%.Â These results indicate that the product developed is declared